Italian validation of the pro-nature conservation behaviour scale (ProCoBS-IT) - Matteo Reho; Giuseppina Spano; Maria Giovanna Massari; Fabiana Sasso; Alessandro Gennaro (Journal for Nature Conservation, 2026)

Optimizing fruit and vegetable by-products/wastes exploitation: diversity, safety and biotechnological innovations based on lactic acid bacteria - Hiba Selmi; Ester Presutto; Vittorio Capozzi; Lucia Bonassisa; Djamel Drider; Ferid Abidi; Giuseppe Spano; Maria Lucia Valeria de Chiara; Mariagiovanna Fragasso (Critical Reviews in Food Science and Nutrition, 2026)

Exploring lactic acid bacteria from fresh fruits, vegetables, and edible flowers: from biodiversity valorisation to food applications - Ester Presutto; Vittorio Capozzi; Maria Lucia Valeria de Chiara; Djamel Drider; Giuseppe Spano; Mariagiovanna Fragasso (World Journal of Microbiology and Biotechnology, 2026)
Fresh plant matrices of food interest host complex microbial communities. Within these microbial ecosystems, biochemical and ecological interactions are relevant in contributing to food quality and safety. In particular, lactic acid bacteria (LAB) play key roles in fermentative processes, bioprotection, and bioactivity. Despite their well-recognised importance in food biotechnology, the ecological dynamics and metabolic versatility of LAB in plant-based environments are still poorly explored. Understanding their diversity and how they adapt to matrix-specific stressors is crucial for identifying new strains with distinctive technological and biofunctional traits. This review summarises a selection of recent studies on LAB associated with fresh plant-derived matrices (i.e., fresh fruits, vegetables, and edible flowers). Particular attention is given to culture-dependent and culture-independent approaches employed for their identification. The main technological and functional aspects are also examined, aiming to assess their properties of interest, including resistance to adverse environmental conditions and mechanisms of microbial interaction. Furthermore, the discussion addresses the main biotechnological applications of selected LAB, including the development of fermented plant-based foods and beverages, the design of probiotic cultures/biocontrol solutions, and the valorisation of plant by-products. To our knowledge, this is the first review to provide an integrated overview of genomic and ecological insights into LAB associated with fresh plant matrices. This approach would help to improve understanding of LAB adaptive dynamics and identify sustainable drivers of innovation in agro-food systems.

Postbiotic Potential of Newly Isolated Riboflavin-Overproducing Lactiplantibacillus plantarum Strains - Angela Scauro; Maria Teresa Rocchetti; Mario Soccio; Barbara la Gatta; Maria Teresa Liberatore; Nicola De Simone; Giuseppe Spano; Daniela Fiocco; Pasquale Russo (Probiotics and Antimicrobial Proteins, 2026)
Lactic acid bacteria (LAB) are food-grade microorganisms able to produce and release bioactive compounds of interest to human health. Some LAB strains can synthesize vitamin B2, i.e., riboflavin, a micronutrient essential for cellular metabolism. In this work, six Lactiplantibacillus plantarum isolated from fruits of the Mediterranean area were exposed to the selective pressure of roseoflavin in order to select spontaneous riboflavin-overproducing phenotypes. The best strains, as determined by the level of riboflavin produced, were characterized for some basic probiotic features, including antibacterial activity, production of organic acids, antibiotic resistance, and survival under digestive stresses using an in vitro gut model. The strain L. plantarum Lp 187_B2 , which produced the highest riboflavin level (6 mg/L), exhibited good resistance to gastro-intestinal stress and a relevant capacity to antagonize undesired bacteria, was selected for additional investigations to assess its capacity to protect intestinal homeostasis. When used as a postbiotic, Lp 187_B2 significantly increased trans-epithelial electrical resistance (TEER) in Caco-2 cell monolayers, an in vitro model of the intestinal barrier. Moreover, in a Caco-2/THP-1 co-culture system, mimicking the inflamed bowel, Lp 187_B2 postbiotics significantly inhibited the release of TNF-α by macrophages, thus pointing to gut-barrier strengthening and potential anti-inflammatory properties. Though a validation in vivo is required, our preliminary results indicate that L. plantarum Lp 187_B2 could be successfully applied as both probiotic and postbiotic formulations for improving human health.

Design, development and qualification of a european international berthing and docking mechanism (IBDM) - Joaquín Meléndez; Jeanette Bast; Johan Bogaerts; Jeremy Bouten; Angelo Costantino; Luc De Busser; Rutger De Nutte; Isabelle De Preter; Andy De Wilde; Felix De Wispelaere; Filip Dewitte; Wim Derkinderen; et al. (Journal of Space Safety Engineering, 2025)

Production of a low alcohol wine with pre-fermentation techniques - Maria Teresa Liberatore; Flavia Dilucia; Mariacinzia Rutigliano; Giuseppe Spano; Felice Teodoro Cota; Barbara la Gatta (Food Bioscience, 2025)

Correction to: The growing link between heatwaves and megafires: evidence from southern Mediterranean countries of Europe - José Maria Costa-Saura; Valentina Bacciu; Costantino Sirca; Onofrio Cappelluti; Donatella Spano; Mario Elia (Natural Hazards, 2025)

The growing link between heatwaves and megafires: evidence from southern Mediterranean countries of Europe - José Maria Costa-Saura; Valentina Bacciu; Costantino Sirca; Onofrio Cappelluti; Donatella Spano; Mario Elia (Natural Hazards, 2025)

Are trait responses of tree species across pyroregions indicative of fire-modulated plant functional strategies? - José Maria Costa-Saura; Gabriele Midolo; Carlo Ricotta; Mara Baudena; Carlo Calfapietra; Mario Elia; Paolo Fiorucci; Simone Mereu; Costantino Sirca; Donatella Spano; Gianna Vivaldo; Gianluigi Ottaviani (Perspectives in Plant Ecology, Evolution and Systematics, 2025)

Polyphenolic characterization, nutritional and microbiological assessment of newly formulated semolina fresh pasta fortified with grape pomace - Maria Teresa Liberatore; Flavia Dilucia; Mariacinzia Rutigliano; Rosaria Viscecchia; Giuseppe Spano; Vittorio Capozzi; Francesco Bimbo; Aldo Di Luccia; Barbara la Gatta (Food Chemistry, 2025)

Probiotic Lactiplantibacillus plantarum strains showing anti-Botrytis activity: A food-grade approach to improve the overall quality of strawberry in post-harvest - Nicola De Simone; Angela Scauro; Danial Fatchurrahman; Maria Luisa Amodio; Vittorio Capozzi; Giancarlo Colelli; Giuseppe Spano; Mariagiovanna Fragasso; Pasquale Russo (Postharvest Biology and Technology, 2024)

Evidence for enduring cardiac and multiorgan toxicity after repeated exposure to the synthetic cannabinoid JWH-018 in male rats - Nicholas Pintori; Maria Pina Serra; Antonio Carai; Carla Lobina; Raffaella Isola; Roberta Noli; Gessica Piras; Enrica Spano; Michael H. Baumann; Marina Quartu; Maria Antonietta De Luca (Toxicology, 2024)

Assessing climate risk for cereals and livestock to inform adaptation planning at regional and local scale - Valentina Mereu; Josè Maria Costa-Saura; Trabucco Antonio; Spano Donatella (Journal of Rural Studies, 2024)

Immunomodulatory Activity on Human Macrophages by Cell-Free Supernatants to Explore the Probiotic and Postbiotic Potential of Lactiplantibacillus plantarum Strains of Plant Origin - Maria Teresa Rocchetti; Pasquale Russo; Nicola De Simone; Vittorio Capozzi; Giuseppe Spano; Daniela Fiocco (Probiotics and Antimicrobial Proteins, 2024)
Upon dietary administration, probiotic microorganisms can reach as live cells the human gut, where they interact with the microbiota and host cells, thereby exerting a beneficial impact on host functions, mainly through immune-modulatory activities. Recently, attention has been drawn by postbiotics, i.e. non-viable probiotic microbes, including their metabolic products, which possess biological activities that benefit the host. Lactiplantibacillus plantarum is a bacterial species that comprises recognised probiotic strains. In this study, we investigated in vitro the probiotic (and postbiotic) potential of seven L. plantarum strains, including five newly isolated from plant-related niches. The strains were shown to possess some basic probiotic attributes, including tolerance to the gastrointestinal environment, adhesion to the intestinal epithelium and safety. Besides, their cell-free culture supernatants modulated cytokine patterns in human macrophages in vitro, promoting TNF-α gene transcription and secretion, while attenuating the transcriptional activation and secretion of both TNF-α and IL-8 in response to a pro-inflammatory signal, and enhancing the production of IL-10. Some strains induced a high IL-10/IL-12 ratio that may correlate to an anti-inflammatory capacity in vivo. Overall, the investigated strains are good probiotic candidates, whose postbiotic fraction exhibits immunomodulatory properties that need further in vivo studies. The main novelty of this work consists in the polyphasic characterisation of candidate beneficial L. plantarum strains obtained from relatively atypical plant-associated niches, by an approach that explores both probiotic and postbiotic potentials, in particular studying the effect of microbial culture-conditioned media on cytokine pattern, analysed at both transcriptional and secretion level in human macrophages.

Estimating annual GHG and particulate matter emissions from rural and forest fires based on an integrated modelling approach - Carla Scarpa; Valentina Bacciu; Davide Ascoli; Josè Maria Costa-Saura; Michele Salis; Costantino Sirca; Marco Marchetti; Donatella Spano (Science of The Total Environment, 2024)

Antimicrobial Properties, Functional Characterisation and Application of Fructobacillus fructosus and Lactiplantibacillus plantarum Isolated from Artisanal Honey - Nicola De Simone; Maria Teresa Rocchetti; Barbara la Gatta; Giuseppe Spano; Djamel Drider; Vittorio Capozzi; Pasquale Russo; Daniela Fiocco (Probiotics and Antimicrobial Proteins, 2023)
Honey is a valuable reservoir of lactic acid bacteria (LAB) and, particularly, of fructophilic LAB (FLAB), a relatively novel subgroup of LAB whose functional potential for human and food application has yet to be explored. In this study, FLAB and LAB strains have been isolated from honeys of different floral origins and selected for their broad antimicrobial activity against typical foodborne pathogenic bacteria and spoilage filamentous fungi. The best candidates, two strains belonging to the species Lactiplantibacillus plantarum and Fructobacillus fructosus , were submitted to partial characterisation of their cell free supernatants (CFS) in order to identify the secreted metabolites with antimicrobial activity. Besides, these strains were examined to assess some major functional features, including in vitro tolerance to the oro-gastrointestinal conditions, potential cytotoxicity against HT-29 cells, adhesion to human enterocyte-like cells and capability to stimulate macrophages. Moreover, when the tested strains were applied on table grapes artificially contaminated with pathogenic bacteria or filamentous fungi, they showed a good ability to antagonise the growth of undesired microbes, as well as to survive on the fruit surface at a concentration that is recommended to develop a probiotic effect. In conclusion, both LAB and FLAB honey-isolated strains characterised in this work exhibit functional properties that validate their potential use as biocontrol agents and for the design of novel functional foods. We reported antimicrobial activity, cytotoxic evaluation, probiotic properties and direct food application of a F. fructosus strain, improving the knowledge of this species, in particular, and on FLAB, more generally.

Use of genetic algorithms in the wavelength selection of FT-MIR spectra to classify unifloral honeys from Sardinia - Marco Caredda; Andrea Mara; Marco Ciulu; Ignazio Floris; Maria I. Pilo; Nadia Spano; Gavino Sanna (Food Control, 2023)

Re-equilibration history and P–T path of eclogites from Variscan Sardinia, Italy: a case study from the medium-grade metamorphic complex - Gabriele Cruciani; Marcello Franceschelli; Chiara Groppo; Giacomo Oggiano; Maria Elena Spano (International Journal of Earth Sciences, 2015)

Behavioural and neurochemical assessment of salvinorin A abuse potential in the rat - Veronica Serra; Liana Fattore; Maria Scherma; Roberto Collu; Maria Sabrina Spano; Walter Fratta; Paola Fadda (Psychopharmacology, 2015)

U–Pb zircon dating and nature of metavolcanics and metarkoses from the Monte Grighini Unit: new insights on Late Ordovician magmatism in the Variscan belt in Sardinia, Italy - Gabriele Cruciani; Marcello Franceschelli; Giovanni Musumeci; Maria Elena Spano; Massimo Tiepolo (International Journal of Earth Sciences, 2013)

Chronic cannabinoid exposure reduces phencyclidine-induced schizophrenia-like positive symptoms in adult rats - Maria Sabrina Spano; Liana Fattore; Francesca Cadeddu; Walter Fratta; Paola Fadda (Psychopharmacology, 2013)

Dipyridamole prevents triple-negative breast-cancer progression - Daniela Spano; Jean-Claude Marshall; Natascia Marino; Daniela De Martino; Alessia Romano; Maria Nunzia Scoppettuolo; Anna Maria Bello; Valeria Di Dato; Luigi Navas; Gennaro De Vita; Chiara Medaglia; Patricia S. Steeg; et al. (Clinical & Experimental Metastasis, 2013)

Motion Compensation in Hand-held Laser Scanning for Surface Modeling in Plastic and Reconstructive Surgery - Paolo Patete; Marco Riboldi; Maria Francesca Spadea; Giuseppe Catanuto; Andrea Spano; Maurizio Nava; Guido Baroni (Annals of Biomedical Engineering, 2009)

Survival of Helicobacter pylori in well water - L. Beneduce; D. Tarantino; G. Spano; M. Libergoli; Maria Labonia; S. Massa (World Journal of Microbiology and Biotechnology, 2003)

Different apoptotic responses and patterns in adhering and floating neoplastic cell cultures: effects of microtubule antagonists - Luigi Sciola; Alessandra Spano; Gianni Monaco; Maria Grazia Bottone; Sergio Barni (Histochemistry and Cell Biology, 2003)

Endogenous risk factors for childhood leukemia in relation to the IGF system (Greece) - Eleni Petridou; Alkistis Skalkidou; Nick Dessypris; Maria Moustaki; Christos Mantzoros; Evangelos Spanos; Dimitrios Trichopoulos (Cancer Causes & Control, 2000)